Lower Limb Exercise-Based Injury Prevention Programs Are Effective in Improving Sprint Speed, Jumping, Agility and Balance: an Umbrella Review - Loïc Bel; Nicolas Mathieu; Vincent Ducrest; Mario Bizzini (North American Sports Medicine Institute, 2021)
# Background Exercise-based injury prevention programs for athletes have demonstrated consistent results in reducing the risk of lower limb injuries. Compliance is essential for program effectiveness and may be facilitated when these programs demonstrate positive effects on athletic performance. # Hypothesis/Purpose To summarize the findings of current systematic reviews on the effectiveness of lower limb injury prevention programs with multiple neuromuscular components on sports performance and quantify these effects. The authors hypothesized that injury prevention programs can improve certain sports performance criteria. # Study Design Umbrella systematic review # Methods Systematic reviews published in French, German, or English between January 1990 and January 2020 were identified in five databases. Only articles that investigated multicomponent lower limb injury prevention programs and their effects on the performance criteria of strength, balance, agility, jumping or speed by both amateur and professional athletes of all ages and sex were included. The methodological quality of the included systematic reviews was assessed by two reviewers independently using the Assessing the Methodological Quality of Systematic Reviews measurement tool. # Results Five systematic reviews met the inclusion criteria. Overall, beneficial effects of multicomponent exercise-based injury prevention programs were observed for balance, agility, jumping and speed. While the effects on strength were more variable, there was a positive trend in favor of injury prevention programs. # Conclusion Injury prevention programs with multiple neuromuscular exercise components demonstrate overall beneficial effects on the performance criteria of balance, agility, jumping or speed. These beneficial effects may be used to promote the implementation of such programs. # Level of Evidence 2a